A MASLOW’S HIERARCHY OF NEEDS-BASED MODEL OF RELIGIOUS MODERATION INTERNALIZATION TO PREVENT RADICALISM AMONG GENERATION Z - Saepuloh, Ade; Manan, Mahmud; Muslihun, Muslihun (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study aims to develop and validate the Integrative Religious Moderation Model based on Maslow’s Hierarchy of Needs (MBIM-RM) as an effective framework for internalizing moderation values to prevent radicalism among Generation Z students. Method: A qualitative multi-case study design was employed at SMAN 1 Garut and SMKN 1 Garut, involving teachers, school leaders, and students selected through purposive sampling. Data was collected via interviews, observations, and document analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. Result: The findings reveal that the internalization of religious moderation occurs through five interrelated stages: contextualization, actualization, role modeling and social habituation, inclusivity-differentiation, and digital externalization, with each stage reflecting the fulfillment of students' psychological, social, and moral needs. Moral development is most effective when schools create an ecosystem that meets students' intrinsic needs for safety, social acceptance, self-esteem, and self-actualization. The integration of digital moral engagement is a significant innovation, as it allows students to develop ethical moral agency in digital environments. Conclusion: Theoretically, MBIM-RM bridges Maslow’s motivation theory, Bandura’s social learning theory, and Berger & Luckmann’s social construction theory, positioning moderation as a dynamic psychosocial ecosystem rather than a static moral attribute. Implication: Practically, this model offers a framework that can be replicated and adapted by educators and policymakers through reflective, participatory learning that is responsive to technological developments. Future research is recommended to use mixed-method and longitudinal approaches, integrating AI-based learning analytics to refine the model in various educational contexts.